Penerapan Model Discovery Learning Untuk Meningkatkan Keaktifan Belajar Siswa Kelas V SD Negeri 2 Sidoharum - Fatkhurrohman Al Hudri, Muhammad Avicena; Fatimah, Siti (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2023)
This study aims to determine the increase in student activity using the discovery learning method in class V SD Negeri 2 Sidoharum. This research is a classroom action research that was carried out for 2 cycles, each cycle consisting of 2 meetings. Each cycle consists of planning, implementation, observation and reflection. The research subjects were fifth grade students of SD Negeri 2 Sidoharum. Data collection techniques using observation and interviews. The data analysis technique uses Miles and Huberman analysis in four stages, namely data collection, data reduction, data presentation and drawing conclusions. The results of the analysis showed that in the first cycle of learning as many as 47.36% of students were actively participate in learning activities. While in the second cycle as many as 78.94% of students actively participate in learning activities. So it can be concluded that there is an increase in student activity in participating in learning activities through the discovery learning method.